THE INFLUENCE OF FINANCIAL LITERACY ON GOLD INVESTMENT DECISIONS-MAKING IN EAST JAVA SOCIETY 2024 - Aqilah, Evelyn Nathania; Maulidina, Hana (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
Financial literacy, which includes knowledge, skills and attitudes towards financial matters, is critical for making sound investment decisions. The research of this study is to investigate the impact of financial literacy on investment decisions, particularly gold investment of East Java in 2024. This study takes a quantitative approach, with data collection carried out through an online questionnaire using Google Forms to assess financial literacy and investment behavior, specifically in gold investment. The correlation method is used to investigate the link between financial knowledge and gold investing decisions. The results of this investigation indicate that there is a positive relationship between financial literacy and gold investment decisions. People with a greater level of understanding of finance more likely to invest in gold and exhibit better informed investment behavior. These findings indicate that increasing financial literacy can help people make better investing decisions, hence enhancing their overall financial well-being.